Long-term exposure to low concentrations of air pollutants and hospitalisation for respiratory diseases: A prospective cohort study in Australia. (December 2018) - Salimi, Farhad; Morgan, Geoffrey; Rolfe, Margaret; Samoli, Evangelia; Cowie, Christine T.; Hanigan, Ivan; Knibbs, Luke; Cope, Martin; Johnston, Fay H.; Guo, Yuming; Marks, Guy B.; Heyworth, Jane; et al.
Abstract: Background: Short- and long-term spatiotemporal variation in exposure to air pollution is associated with respiratory morbidity in areas with moderate-to-high level of air pollution, but very few studies have examined whether these associations also exist in areas with low level exposure. Objectives: We assessed the association between spatial variation in long-term exposure to PM2.5 and NO2 and hospitalisation for all respiratory diseases, asthma, chronic obstructive pulmonary disease (COPD), and pneumonia, in older adults residing in Sydney, Australia, a city with low-level concentrations. Methods: We recorded data on hospitalisations for 100, 084 participants, who were aged >45 years at entry in 2006–2009 until June 2014. Annual NO2 and PM2.5 concentrations were estimated for the participants' residential addresses and Cox proportional hazards regression was used to model the association between exposure to air pollutants and first episode of hospitalisation, controlling for personal and area level covariates. We further investigated the shape of the exposure-response association and potential effect modification by age, sex, education level, smoking status, and BMI. Results: NO2 and PM2.5 annual mean exposure estimates were 17.5 μg·m −3 and 4.5 μg·m −3 respectively. NO2 and PM2.5 was positively, although not significantly, associated with asthma. The adjusted hazard ratio for a 1 μg·m −3 increase in PM2.5 was 1.08, 95% confidence interval 0.89–1.30. The adjusted hazard ratio for a 5 μg·m −3 increase in NO2 was 1.03, 95% confidence interval 0.88–1.19. We found no positive statistically significant associations with hospitalisation for all respiratory diseases, and pneumonia while negative associations were observed with COPD. Conclusions: We found weak positive associations of exposure to air pollution with hospitalisation for asthma while there was no evidence of an association for all respiratory diseases. Highlights: NO2 and PM2.5 were weakly associated with hospitalisation for asthma No associations were found with hospitalisation for all respiratory diseases, and pneumonia Effects of air pollution on asthma may persist at low levels of air pollution Negative associations were observed with hospitalisation for COPD